Development of an efficient statistical volumes of fluid–Lagrangian particle tracking coupling method. (4th February 2014) - Grosshans, H.; Szász, R.‐Z.; Fuchs, L.
SUMMARY The breakup of a liquid jet into irregular liquid structures and droplets leading to the formation of a dilute spray has been simulated numerically. To overcome the shortcomings of certain numerical methods in specific flow regimes, a combined approach has been chosen. The intact liquid core, its primary breakup and the dense spray regime are simulated using the volumes of fluid (VOF) method in combination with LES, whereas the Lagrangian particle tracking (LPT) approach in the LES context is applied to the dilute spray regime and the secondary breakup of droplets. A method has been developed to couple both simulation types on a statistical basis. This statistical coupling approach (SCA) reflects the dominating physical mechanisms of the two‐phase flow in each regime to a high degree. The main benefit of the SCA is computational efficiency as compared with the more straightforward approach where one follows each structure, denoted here as the direct coupling approach. The computational benefits stem from the reduction of computational time since the VOF simulation is run only until statistical convergence and not during the whole spray development. A second benefit using the SCA is the possibility to use the stochastic parcel method in the LPT simulation whereby a large number of droplets may be handled. The coupling approach is applied to the atomization of a fuel jet in a high pressure chamber, demonstrating the gain of efficiency of the SCA as compared with direct coupling approach. Copyright © 2014 The Authors. International Journal for Numerical Methods in Fluids published by John Wiley & Sons Ltd.